Microbial contamination level of water supply system at the Faculty of Dentistry, USIM, Malaysia - Normaliza Ab. Malik; Rohazila Mohd Hanafiah; Wan Mohamad Nasir Wan Othman (Universiti Kebangsaan Malaysia, 2013)
This study was to evaluate the microbial contamination level in direct water supply at the Polyclinic, Faculty of Dentistry, USIM, Malaysia. Water samples were collected randomly from water supplied via the cup filler outlet of 20 dental units and 20 side water taps at Level 16 and 17 of Polyclinic, Faculty of Dentistry, USIM. All the samples were placed and spread evenly on the surface of prepared agar media (the nutrient agar) using the spread technique. Each sample consists of 0.5 mL water. The microbial count was done using a magnifying glass and the total number of bacteria concentration was reported as colony forming unit in 1 mL of water (cfu/mL). In this study water from an aquarium was used as positive control with 220 cfu/mL, while the distilled water taken from the CSSD was used as negative control with no colony of microorganism. The study demonstrated that there were low contamination before the treatment that was beginning of the session in water supplied via the cup filler outlet and side water tap from the sink with 2 cfu/mL. However, two cup fillers water and one side water taps from Polyclinic level 17 showed a slightly higher bacterial colonies with 4 cfu/mL and 6 cfu/mL of microbes. At the end of the session, result showed that higher bacterial count from Polyclinic level 17 than Polyclinic level 16 with the highest reading of 40 cfu/mL. The findings were considered low and the water was safe for the dental procedures. The quality of water supplied at the Faculty of Dentistry, USIM was within the limits recommended by the American Dental Association, i.e. bacterial loads of not more than 200 cfu/mL for dental procedures.